Crude Oil Degrading Bacteria: Isolation, Growth and Biodegradation Studies - Ali, Farag M. (1998)
A total of 61 bacteria isolates were isolated from the four soil samples during the primary screening using 0.1% crude oil (v/v) as sole carbon source by the direct plating and enrichment method. However, only 23 isolates gave good growth when grown in 1% crude oil out of which 9 . isolates were able to grow in crude oil up to 50% concentration. Substrate specificity studies done on 5 of the 9 isolates, showed that all the 5 isolates (170, 181, 183, 217 and 224) were able to grow on all the 10 different hydrocarbon substrates tested with varying preferences. Optimum growth for a/l the 5 isolates were observed at 30°C, pH 7.5, with 1% nitrogen and phosphorous supplements and shaken at 150 rpm. They were able to grow in media containing up to 2.3% NaCI concentration. Among the 5 isolates, isolate 170 gave the highest 00540 reading (0.469) and viability count (1.9x107) after 5 days. Isolates 217 and 183 gave the lowest growth with 00540 and viability count after 5 days, respectively. Infrared spectrometry (IR) analysis showed that all the 5 isolates caused some peaks reduction, disappearance, appearance and intensification after 7 days incubation. Biochemical and morphological studies on the 5 isolates revealed that isolate 170, 183 and 217 belong to Bacillus sp, while, isolates 181 and 224 are Pseudomonas sp. Detailed biochemical identification indicate that isolate 170 is Bacillus subtilis and isolate 181 is Pseudomonas aeruginosa.